Volatilidade de óleos essências no controle de fusarium oxysporum em sementes de tomate cereja - Russiano, Carlos Guilherme dos Santos (2020)
Fusarium oxysporum is the causative agent of Fusarium wilt in tomato, one of the ways to control the disease is through chemical treatment of seeds, however the present work seeks an alternative solution to chemical treatment, using the purging technique with essential oils. The objective of the work is to evaluate the effect of purge with essential oils of tea tree, chia, citronella, lavender, anise and clove lavender in cherry tomato seeds contaminated with Fusarium oxysporum. The experiments were carried out at UTFPR, Dois Vizinhos campus, in the phytopathology and seed laboratories. Organic cherry tomato seeds, batch 118074-001-52 from ISLA were used. In all experiments, a completely randomized design with four replications was used. After contact of the seeds with the inoculum in Petri dishes for a period of 24 hours, followed by purging them with essential oils, the gerbox germination test was performed with 25 seeds in each experimental unit, for a period of 8 days, checking the variables IVG,% G, TMG. With the same seeds, mycelial growth was evaluated, in order to verify its influence on the phytopathogen morphology, for this, a seed from each treatment was placed in the center of a Petri dish, where mycelial growth was measured; and then samples of each treatment were observed in a scanning electron microscope. After confirming the best treatment, through the results obtained, tea tree oil was again submitted to the germination test, where 25 seeds of each treatment composed of the cherry tomato seeds in contact with the pathogen in the petri dishes for 24 hours and purged for another 24 hours with tea tree essential oil in closed crucibles; plus the positive control in which seeds without inoculum were used, and the negative control, containing only the seeds with the inoculum of F. oxysporum; in which every three days four gerboxes from each treatment were opened to check the percentage of germination of the seeds, number of abnormal seeds and percentage of presence of mycelium in the seeds, and then collected in plastic bags and taken to the freezer to later proceed the resistance induction tests in seedlings, through the analysis of chitinase, glucanase and total proteins. The results obtained were submitted to the Tukey test (P≤0.05), and the regression analysis, through the computational tool Genes. The final data showed that tea tree oil can inhibit the mycelial growth of F. oxysporum, without harming the germination of cherry tomato seeds. Subsequent tests with this oil also demonstrate that with the oil there is a reduction of mycelium in the seeds and a reduction of abnormal seedlings in comparison with the negative control. There was no significant difference between the variables tested for resistance induction.